Adolescents' thoughts and feelings about the local and global environment: a qualitative interview study. Issue 1 (15th November 2021) - Thompson, Rhiannon; Fisher, Helen L.; Dewa, Lindsay H.; Hussain, Tania; Kabba, Zaina; Toledano, Mireille B.
Abstract : Background: Despite a recent increase in engagement with environmental issues among young people, their impact upon adolescent mental health and wellbeing is not yet fully understood. Therefore, this study aimed to explore adolescents' thoughts and feelings about current environmental issues. Methods: Semi‐structured interviews were conducted with a convenience sample of 15 UK‐based adolescents aged 14–18 years (66.7% female). Transcripts were inductively thematically analysed by the interviewing researcher and two adolescent co‐researchers, with priority given to the co‐researchers' impressions to strengthen interpretations of the personal experiences of the interviewees. Results: Six themes were identified: the local environment, efficacy, challenging emotions, information, hindrances and perceptions of the future. The local environment was found to affect adolescents positively and negatively. Factors including greenspace and fresh air had a positive impact, and factors including noise and litter had a negative impact. Most participants reported feeling disempowered to personally influence environmental problems but were engaged with them and felt that trying to make a difference was beneficial for their wellbeing. Adolescents largely reported negative expectations about the environment's future. Conclusion: The UK adolescents interviewed appeared to be very engaged and emotionally affected by a perceived lack of care towards the environment, locally and globally. It is therefore imperative to amplify young people's voices and involve them in influencing environmental policy, for the benefit of young people and the planet. Further research should quantify the extent to which environmental issues affect young people's mental health and identify factors that could prevent or alleviate distress.